Imperial trophy or island relict? A new extinction paradigm for Père David's deer: a Chinese conservation icon. Issue 10 (25th October 2017) - Turvey, Samuel T.; Barnes, Ian; Marr, Melissa; Brace, Selina
Abstract : Determining the 'dynamic biogeography' of range collapse in threatened species is essential for effective conservation, but reconstruction of spatio-temporal patterns of population vulnerability and resilience can require use of non-standard ecological data such as historical archives. Père David's deer or milu, one of the few living mammal species that has become extinct in the wild, is historically known only from a small captive herd of unknown provenance that survived until 1900 in the Imperial Hunting Park near Beijing, from which all living individuals are descended. Using ancient DNA analysis, we demonstrate that two fawns collected in 1868 from Hainan Island, off the southern Chinese mainland, represent the only known wild milu specimens and were sampled from probably the last wild population. The Hainan milu population shows extremely low genetic differentiation from descendants of the Beijing herd, suggesting that this now-extinct population may have been the source of the captive herd. This revised extinction model refutes the supposed long-term survival of a captive milu herd for centuries or millennia after final extinction of wild populations, highlighting the vulnerability of remnant mammal populations in the absence of proactive management and the importance of historical museum collections for providing unique new insights on evolution, biogeography and conservation. Milu experienced a pattern of final population persistence on an island at the periphery of their former range, consistent with the 'range eclipse' or 'contagion' model of range collapse, and matching the spatial extinction dynamics of other extinct mammals such as the thylacine and woolly mammoth.